5‐aminomethyloxazolidine‐2, 4‐dione hybrid α/β‐dipeptide scaffolds as inductors of constrained conformations: Applications to the synthesis of integrin antagonists. Issue 5 (September 2015) - De Marco, Rossella; Mazzotti, Giacomo; Dattoli, Samantha D.; Baiula, Monica; Spampinato, Santi; Greco, Arianna; Gentilucci, Luca
ABSTRACT: Peptidomimetics represent an attractive starting point for drug discovery programs; in particular, peptidomimetics that result from the incorporation of a heterocycle may take advantage of increased enzymatic stability and higher ability to reproduce the bioactive conformations of the parent peptides, resulting in enhanced therapeutic potential. Herein, we present mimetics of the α4β1 integrin antagonist BIO1211 (MPUPA‐Leu‐Asp‐Val‐Pro‐OH), containing a aminomethyloxazolidine‐2, 4‐dione scaffold (Amo). Interestingly, the retro‐sequences PhCOAsp(OH)‐Amo‐APUMP including either (S)‐ or (R)‐configured Amo displayed significant ability to inhibit the adhesion of α4β1 integrin expressing cells, and remarkable stability in mouse serum. Possibly, the conformational bias exerted by the Amo scaffold determined the affinity for the receptors. These peptidomimetics could be of interest for the development of small‐molecule agents effective against inflammatory processes and correlated autoimmune diseases. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 104: 636–649, 2015.